1999
DOI: 10.1021/cm990174j
|View full text |Cite
|
Sign up to set email alerts
|

Silane Activation by Ti(NMe2)4 and NH3 during Chemical Vapor Deposition of Ti−Si−N Films

Abstract: Molecular beam mass spectrometry has been used to observe the activation of silane, predominantly in the gas phase, during the chemical vapor deposition of Ti-Si-N thin films using Ti(NMe 2 ) 4 , tetrakis(dimethylamido)titanium, silane, and ammonia at 450 °C. The extent of silane reactivity was dependent upon the relative amounts of Ti(NMe 2 ) 4 and NH 3 . Ti-Si-N thin films were deposited using similar process conditions as the molecular beam experiments. RBS and XPS were used to determine the atomic composit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…2 Due to the importance of TDMAT, the reaction of organotitanium compounds in the gas phase has been studied both theoretically 5,22,34,35 and experimentally. 20,24,28,[36][37][38][39][40] Another important focus of applied research involved has been on the reaction of TDMAT with different substrates such as metals, nitrides, and silica. 20,21,[23][24][25][26][27]29,38,[41][42][43] However, in spite of the importance of the interaction of TDMAT with the technologically relevant Si(100) surface, studies of the system TDMATSi(100) are very scarce.…”
Section: Introductionmentioning
confidence: 99%
“…2 Due to the importance of TDMAT, the reaction of organotitanium compounds in the gas phase has been studied both theoretically 5,22,34,35 and experimentally. 20,24,28,[36][37][38][39][40] Another important focus of applied research involved has been on the reaction of TDMAT with different substrates such as metals, nitrides, and silica. 20,21,[23][24][25][26][27]29,38,[41][42][43] However, in spite of the importance of the interaction of TDMAT with the technologically relevant Si(100) surface, studies of the system TDMATSi(100) are very scarce.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, previous results from our group demonstrated that gas-phase chemistry during CVD of titanium silicon nitride (Ti−Si−N) from tetrakis(dimethylamido)titanium (TDMAT or Ti(N(CH 3 ) 2 ) 4 ), NH 3 , and SiH 4 is critical. Most importantly, it was established that TDMAT activates silane in the presence of ammonia at 723 K . The amount of silane activation is dependent upon the relative amounts of TDMAT and ammonia.…”
Section: Introductionmentioning
confidence: 99%
“…19 Silicon titanium nitride coatings or layers are prepared mainly by chemical vapor deposition (CVD). 20,21 These silicon titanium nitride powders and layers are typically produced in dense forms, which can be used as structural and/or wear-resistant materials due to their high hardness and creep resistance. 22 Our interest is to develop new micro-and mesoporous nonoxide materials with high surface area accessible for applications in heterogeneous catalysis.…”
Section: Introductionmentioning
confidence: 99%